SPECIAL STATUS MINOR OF THE SUBJECT OF ADMINISTRATIVE RESPONSIBILITY - Roman Vladimirovich, Кимлык (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The paper studied the legal aspects of the definition of a minor, as the actor responsible for an administrative offense. The main age, psychological, historical and ethnic factors affecting these legal actors. Analyzed the existing rules of law that determine the threshold age at which comes administrative responsibility and portfolio theorists in this field. Recommendations for improving the legislation to incorporate not only the actual age of the subject, but the possibility to realize the significance of their actions.